Over land and over sea domestic trade frictions in the Philippines. (Asian Development Bank, 2019)
ADB, in collaboration with UN Environment, prepared this tool compendium to help developing countries implement the environmental dimensions of the Sustainable Development Goals.The tools presented here can help policy makers gain a better understanding of Sustainable Development Goal (SDG) interlinkages, establish horizontal and vertical policy coherence, and select appropriate guidelines, indicators, and institutional arrangements for effective integration into national policies, plans, and programs. This publication reflects the high-level commitment of ADB and UN Environment to support efforts to accelerate progress in implementing the environmental dimensions of the SDGs.